Spatial variation and community composition of phytoplankton along the Pahang estuary, Malaysia - Khan Chowdhury, Ahmed Jalal; Mohamed, Ahmad Azfar; John, Akbar; Yunus, Kamaruzzaman (A N S I Network, 2011)
The aim of this study was to examine the phytoplankton patchiness, as expressed by community composition and their diversity during the monsoon and Non-monsoon seasons along the Pahang estuary, Malaysia during 2008. Three zones in the estuary were sampled on both the seasons covering both upstream and downstream of the estuary. Among the identified 42 genera of phytoplankton, the most dominant phytoplankton were Leptocylindrus sp. (19.05%), Lauderia sp. (11.02%) and Skeletonema sp. (10.32%) of total abundance. The least dominant or rare phytoplankton were Ditylum sp. (0.05%), Asterionella sp. (0.04%), Gyrosigma sp. (0.05%), Gymnodinium sp. (0.04%) and Prorocentrum sp. (0.07%) of total abundance. The statistical analysis showed that there was no significant difference in diversity of phytoplankton between different zones (p>0.05). Result indicated that many of the phytoplankton species inhabiting in Pahang estuary were sensitive to salinity fluctuation. The increased diversity during monsoon might be due to the runoff water that probably brought the phytoplankton of other freshwater sources. Physicochemical parameters showed significant variation between different zones (p<0.05) except for temperature. Present study clearly showed that phytoplankton community in Pahang estuary was quiet diverse during monsoon and dominant during non monsoon season.